De facto and official exchange rate regimes in transition economies - Jürgen von Hagen; Jizhong Zhou (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
This paper provides an empirical investigation on the discrepancies between official exchange rate regimes and de facto exchange rate policies in transition economies. Since official and de facto regime choices are not independent of each other, we adopt a bivariate probit model to describe the joint determination of the two regime choices. After finding the important determinants of both regime choices, we use a univariate probit model to describe the determination of regime discrepancies. We find that errors in the selection of official regimes as well as the macroeconomic developments calling for conflicting adjustments in exchange rate regimes are important determinants of regime discrepancies.
Keywords: 330; Wechselkurssystem; Wechselkurspolitik; Übergangswirtschaft; Schätzung; Osteuropa